Effects of a non-circular chainring on sprint performance during a cycle ergometer test - Hintzy, F.; Grappe, F.; Belli, A. (Journal of Sports Science & Medicine, 2016)
Non-circular chainrings have been reported to alter the crank angular velocity profile over a pedal revolution so that more time is spent in the effective power phase. The purpose of this study was to determine whether sprint cycling performance could be improved using a non-circular chainring (Osymetric: ellipticity 1.25 and crank lever mounted nearly perpendicular to the major axis), in comparison with a circular chainring. Twenty sprint cyclists performed an 8 s sprint on a cycle ergometer against a 0.5 N/kg-1 friction force in four crossing conditions (non-circular or circular chainring with or without clipless pedal). Instantaneous force, velocity and power were continuously measured during each sprint. Three main characteristic pedal downstrokes were selected: maximal force (in the beginning of the sprint), maximal power (towards the middle), and maximal velocity (at the end of the sprint). Both average and instantaneous force, velocity and power were calculated during the three selected pedal downstrokes. The important finding of this study was that the maximal power output was significantly higher (+ 4.3%, p < 0.05) when using the non-circular chainring independent from the shoe-pedal linkage condition. This improvement is mainly explained by a significantly higher instantaneous external force that occurs during the downstroke. Non-circular chainring can have potential benefits on sprint cycling performance.